2013
DOI: 10.1038/jhg.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for Fabry disease in Japan: prevalence and genotypes of Fabry disease in a pilot study

Abstract: Fabry disease (FD) is an X-linked lysosomal storage disorder caused by a deficiency of α-galactosidase A (GLA) activity. Enzyme replacement therapy (ERT) for FD is available, and newborn mass screening for FD is being implemented. Here, we undertook a pilot study of newborn mass screening for FD in Japan. GLA activity in dried blood spots was measured using a fluorescence assay and confirmed by measurement of GLA activity in white blood cells (WBCs) in infants with abnormally low GLA activity. This was followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 33 publications
1
65
1
1
Order By: Relevance
“…It is indicated that the enzyme activity is relatively higher and the clinical symptoms of Fabry disease are poor. The frequency of Fabry disease in our country is not clear, but from recent epidemiological study results, it is presumed to be about one in 7000 newborns [30]. Because this is progressive disease that causes patients to develop renal failure in their 30s when they are active in society and often causes cardiac failure in their 40s [31], efficacious treatments have been desired; however, as mentioned above, enzyme replacement therapy has been developed for the disease and it is expected that the prognosis will improve with therapy [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 91%
“…It is indicated that the enzyme activity is relatively higher and the clinical symptoms of Fabry disease are poor. The frequency of Fabry disease in our country is not clear, but from recent epidemiological study results, it is presumed to be about one in 7000 newborns [30]. Because this is progressive disease that causes patients to develop renal failure in their 30s when they are active in society and often causes cardiac failure in their 40s [31], efficacious treatments have been desired; however, as mentioned above, enzyme replacement therapy has been developed for the disease and it is expected that the prognosis will improve with therapy [32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 91%
“…155 Additional pilot studies in the region for other LSDs (Niemann-Pick A/B, Krabbe, Gaucher, Fabry, and Hurler syndrome) have been reported. [156][157][158][159] Other conditions for which there have been ongoing NBS pilot studies include citrin deficiency, 160 SCID, 161 Fragile-X syndrome, 162 X-ALD, 44 and Wilson's disease. 163 Currently, Taiwan is the only country in the region that includes both Pompe disease and SCID in the national panel of conditions.…”
Section: Asia Pacificmentioning
confidence: 98%
“…21 These fluorometric assays used commercially available fluorogenic (4-methylumbelliferone) substrates and were adopted for NBS pilot studies, usually with small modifications, of Fabry disease and/or Pompe disease in Italy, Taiwan, and Japan. 8,9,[22][23][24][25] In Taiwan, 2 NBS laboratories implemented a fluorometric assay for routine screening for Pompe disease but one switched to MS/MS in 2010. 25,26 The switch to MS/MS was possible because, in collaboration with Chamoles, Michael Gelb, C. Ronald Scott, and others developed enzyme-specific substrates, synthesized isotopically labeled substrates, and measured the products of various enzyme reactions simultaneously in DBS with MS/ MS. 27 Since the first description of their Flow Injection Analysis (FIA) MS/MS assay, modifications including the number of enzymes, sample preparation steps, and the addition of liquid chromatography (LC) have been reported and applied in both limited studies and routine NBS.…”
Section: Newborn Screening Assays For Lsdsmentioning
confidence: 99%